Co-administration of α-GalCer analog and TLR4 agonist induces robust CD8(+) T-cell responses to PyCS protein and WT-1 antigen and activates memory-like effector NKT cells - Coelho-Dos-Reis, Jordana G (Clinical immunology (Orlando, Fla.), 2016)
Copyright © 2016 Elsevier Inc. All rights reserved.